MENGENAL SISTEM INFORMASI MANAJEMEN DAKWAH (PENGERTIAN SISTEM, KARAKTERISTIK SISTEM) - Erwan Effendy; Elsa Adelia Siregar; Putri Chairina Fitri; Ibnu Alif Syahbana Damanik (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Information can be likened to blood that flows in the human body, so it is the same as in a company that information is very important for the development and progress of a company. If the company is lacking or late getting information it will be fatal. It will be difficult for companies to develop, it is difficult to manage human resources, and it is difficult to make company strategic decisions and this can cause companies to be unable to compete with their competitors. So understanding a basic concept in an information system is very important for designing an information system so that it can be effective. So preparing steps or methods to provide quality and useful information is a major goal in designing an information system so that goals are achieved